Study of lineament density in potential evaluation of rock fall in Kinta Valley Kajian ketumpatan lineamen dalam penilaian potensi jatuhan batuan di kawasan Lembah Kinta - Ghani, M.F.A. (Penerbit Universiti Kebangsaan Malaysia, 2016)
Limestone hills in Kinta Valley formed a prominent natural beauty to the landscape due to its unique features formed by dissolution of carbonate rocks. However, depending from where the hill is situated, it may exposes threat to humans and properties due to the existence of many geological structures such as extensive joints and fractures. The purpose of this study was to examine the relationship between lineament density map and stability of seven limestone hills in Kinta Valley, Malaysia. Methods in this study were divided into two stages, namely the lineament density map and evaluation of the slope stability using the rock mass strength (RMS) method. A total of 599 lineaments were identifed with the total length of 317 km. Lineament density map is further classifed into three classes: Low (137.0-84.23), medium (84.22-46.83) and high (46.82-0.0). The purpose of RMS is to validate rockfall susceptibility as portrayed in the lineament density map. A total of 12 assessment stations for each of the hills were conducted using the rock mass strength system (RMS). The geological conditions of the hills were assessed by using seven components of the RMS, these are intact rock strength, weathering, joint width, joint orientation, joint width, discontinuity and ground water fow. Subsequently, the hills are classifed into very strong, strong, moderate, weak, or very weak based on the sum of ratings for all the components. The results observed in the feld showed that almost all stations are classifed into the medium class (Gunung A, Rapat, Datok, Lang, Kandu, Panjang and Tempurung), only one station (Gunung Lang) is classifed in the weak class. The lineament density map and the RMS scores are correlated well with 73 accuracy. This shows that the stability of slopes in Kinta Valley is directly affected by regional lineament density.